Psychological Training of Kurash Wrestlers - Abdumalik ougli, Nomozov Suyunbek (European Journal of Life Safety and Stability (2660-9630), 2022)
A number of specialists in sports psychology see the essence of the psychological readiness of a wrestler in a variety of effects on him of difficult conditions of competitive activity and the ability to make the best decision in time in the current situation, in the unity of activity and state, in constant monitoring of behavior.